(untitled) (Journal of Nuclear Technology in Applied Science, 2024)
This experiment was conducted to study the effect of heat stress on some reproductive and productive performance in purebred and crossbred female goats under both of hot (summer season) and mild climatic (winter season) conditions. Forty mature female goats (20 Baladi and 20 crossbred (50% Zaraibi x 50% Baladi) used in this research. Results - cundity were higher in experimental does during mild climate conditionsthan hot climate conditions. Birth weight recorded higher values in mild climate conditions in comparison with hot climate conditions. Concerning to breed, reproductive traits were higher in crossbred goat does compared with purebred goat does. Crossbred goat does showed higher (P<0.01 or P<0.0001) in all productive traits than Baladi goat does. Cortisol hormone concentration showed lower (P<0.0001) concentration under mild climate conditions than hot climate conditions during different stages of estrous cycle, pregnancy and postpartum periods. On the other in crossbred goat does compared with purebred does during different stages of estrous cycle, except diestrous period. Similar trend was found during pregnancy and postpartum periods (P<0.01 or P<0.0001). It could productive and productive traits of goats and in the same time, crossbred was better than purebred goats.